Cost-Benefit analysis of educational tourism in North Cyprus: A qualitative study of the socio-economic impacts - Rezapouraghdam, Hamed; Behravesh, Elaheh; Ari, Engin; Doh, Winifred Lema (Texas A and M University kangjae@tamu.edu, 2018)
Educational tourism continually commands attention in the academic sphere around the world. In contrast to previous studies that have mostly relied on figures and numbers to assess the socio-economic impacts of educational tourism, this study makes a two-fold contribution to the literature. Firstly, empowered by the cost-benefit theoretical framework and a qualitative research approach using semi-structured interviews, this study identifies the socio-economic pros and cons of this phenomenon as experienced by different entrepreneurs in Famagusta city: an educational tourism destination in North Cyprus. Secondly, the specific attribute of Famagusta, a destination that hosts a considerable number of educational tourists in comparison to the local population, has created an opportunity to see how this industry affects the economy of such a region. A total number of 24 interviewees were selected purposefully as the study sample, and the results showed that educational tourism and the economic lives of the local community are firmly tied together. © 2018, Texas A and M University.
Keywords: Educational tourism; North Cyprus; Qualitative research; Socio-economic impacts